Evolutionary Signature and Genetic Structure of Concatenated TP53-CYP17A1 Genes in Colorectal Cancer in Senegal - Ndong, Anna; Keneme, Bineta; Sembene, Mbacké (European Journal of Applied Sciences, 2026)
This study aims to characterize the mutational profiles of the TP53 and CYP17A1 genes in Senegalese patients with colorectal cancer (CRC) in order to better understand the local molecular mechanisms of tumorigenesis. The analysis included 24 patients with CRC and 24 healthy controls. The sequences of exon 4 of TP53 and the promoter region at exon 1 of CYP17A1 were concatenated, then subjected to genetic structuring, historical demography, and phylogenetic relationship analyses using DnaSP (v5.10), MEGA (v7.014), and Arlequin (v3.1). The results reveal significant genetic differentiation between cancerous and healthy tissues (FST = 0.113, p = 0.009), as well as greater genetic diversity within tumors. Neutrality tests (Tajima’s D and Fu’s FS) indicate recent demographic expansion in the tumor population, with an excess of rare variants. The multimodal distribution of mismatches and the haplotype network confirm this evolutionary dynamic, marked by the emergence of haplotypes specific to cancerous tissues. These data suggest that the accumulation of mutations in TP53 and CYP17A1 contributes to genetic heterogeneity and CRC progression in the Senegalese population, opening up prospects for targeted therapeutic approaches.